Applying Insights from Cultural Studies to Adult Education: What Seinfeld Says About the AERC - Nod Miller (Adult Education Research Conference, 1999)
The zany adventures of a glamorous British professor who goes to an important international conference but spends most of her time searching for a TV in order to watch her favourite sitcom. Despite her commitment to 'no hugging, no learning', she gains some profound insights into mass culture, adult education, friendship and postmodernity as a result. Parental guidance suggested.